2010
DOI: 10.1007/s00431-010-1286-4
|View full text |Cite
|
Sign up to set email alerts
|

Poor adherence to antibiotic prescribing guidelines in acute otitis media—obstacles, implications, and possible solutions

Abstract: Many countries now have guidelines on the clinical management of acute otitis media. In almost all, the public health goal of containing acquired resistance in bacteria through reduced antibiotic prescribing is the main aim and basis for recommendations. Despite some partial short-term successes, clinical activity databases and opinion surveys suggest that such restrictive guidelines are not followed closely, so this aim is not achieved. Radical new solutions are needed to tackle irrationalities in healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 81 publications
(101 reference statements)
1
20
0
Order By: Relevance
“…Bearing in mind the lack of increase in the incidence of AM, this may indicate previous overdiagnosis and overtreatment of AOM. Declining consumption of antibiotics and patients consultations in cases of suspected AOM have also been reported from other countries together with poor compliance with guidelines for treating AOM [24][25][26].…”
Section: Discussionmentioning
confidence: 85%
“…Bearing in mind the lack of increase in the incidence of AM, this may indicate previous overdiagnosis and overtreatment of AOM. Declining consumption of antibiotics and patients consultations in cases of suspected AOM have also been reported from other countries together with poor compliance with guidelines for treating AOM [24][25][26].…”
Section: Discussionmentioning
confidence: 85%
“…However, studies reviewed by Haggard et al. (30) have shown that the adherence of physicians to these guidelines is poor in Europe. In the Netherlands, OM is primarily treated by general practitioners, who have their own guidelines for the treatment with antibiotics; the Dutch guideline recommends prescribing antibiotics in selected cases of OM, that is, those at risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics also have known harms and antibiotic resistance is increasing worldwide. Therefore, ‘watchful waiting’ or ‘expectant observation’ is either recommended or considered reasonable in guidelines for the management of uncomplicated AOM in children aged over 2 years in Australia,1 Canada,2 France,2 Germany,2 Scotland,2 Spain,2 the Netherlands,2 UK2 and the USA 3…”
Section: Contextmentioning
confidence: 99%